Determination of the Efficiency of Hydrocarbon Flow in the Onshore Tshiende-07 Well of the Coastal Basin of The Democratic Republic of the Congo - Lingwangasa Masaka; Matamba Raphael; Kabuya Faurysse; Longongo Rosy; Opuluku Rachidi; Ruth Ilunga Mulaji; Naomie Bokonda Nongote; Mabeni Steeves; Manzembele Lose; Tambashie César; Richard Kangiama Lwangi; Djonive Munene (Analecta)
The general objective of this work is to determine the efficiency of the flow of hydrocarbons in the Tshiende 07 Well. To do this, we have set ourselves the following specific objectives: To carry out a study of the performance of Tshiende 07 wells; Calculate the productivity index of the Tshiende 07 well; Calculate the maximum flow rate in the Tshiende 07 well; Draw the Inflow Performance Relationship (IPR) curve; Determine the hydraulic parameters of the flow of hydrocarbons in a well; Draw the Tubing Performance Relationship (TPR) curve; Apply nodal analysis in the TS-07 well. As we have developed the different mathematical approaches for the optimization of the flow of hydrocarbons in a producing well, we exploited the Poettman-Carpenter mathematical approach, and since iterative calculations of this approach are tedious, we used the Poettmann-carpenter BH-xls software to know the evolution of the pressure in the tubing as a function of depth and Botthom Oil Nodal BH-xls to draw the Tubing Performance Relationship (TPR) curve and to determine the operating points between the curve IPR and TPR during nodal analysis.